On the Issue of Evaluating the Cost of Objects of Computer Forensics - Nikolai А. Khatuntsev (Теория и практика судебной экспертизы, 2021)
The rapid development of computer technologies poses new challenges to experts and requires solving new tasks. The article addresses the issue of determining the cost of objects when conducting forensic computer examinations. The author considers some approaches to determining the market value of the most popular objects (computer tools, an organization’s website) at a specific time, particularly at the time of the crime. The author justifies the notion that the resolution of such issues should be a part of a forensic expert’s specialized knowledge of information and computer technologies since this contributes to solving the tasks of this kind of examination and fulfilling the principles of forensic expertise.